Evaluation of aberrantly glycosylated cancer antigen 19-9 as a novel prostate cancer biomarker - Relander, Emma (My University, 2026)
Prostate cancer (PCa) is the most common cancer in men and the second leading cause of cancer-related mortality in men over fifty years old. The widely used PCa screening method is a prostate-specific antigen (PSA) blood test, which, however, has limited specificity. This thesis aimed to evaluate the potential of aberrantly glycosylated cancer antigen 19-9 (CA 19-9) as a novel PCa biomarker to overcome difficulties with PSA testing and to identify proteins expressed in PCa. Time-resolved fluorescence immunoassays in which europium-doped nanoparticles were coated with different lectins were used to identify CA 19-9 glycovariants in PCa patients compared to individuals with benign prostatic hyperplasia (BPH). Additionally, lectins and anti-CA 19-9 antibody fragments were used to identify proteins from extracellular vesicles derived from PCa and BPH plasma sample pools. The glycovariant immunoassays, which detect aberrantly glycosylated CA 19-9, combined with total-PSA values better discriminated the PCa from BPH individuals when utilizing macrophage galactose-type lectins (p = 1.2 x 10-8) as well as mannose-binding lectins (p = 1.8 x 10-8) compared to the total-PSA values alone (p = 1.8 x 10-7). Additionally, proteins bound to anti-CA 19-9 or to anti-mannose-binding lectins specific to PCa were identified. The aberrantly glycosylated CA 19-9 could be a novel PCa biomarker when combined with total-PSA values, but further studies with known disease histories are needed to confirm it.
Keywords: prostate cancer; cancer antigen 19-9; prostate-specific antigen; benign prostatic hyperplasia; glycosylation; lectins; time-resolved fluorescence immunoassays